Surface Electrical Behaviors of Apatite, Dolomite, Quartz, and Phosphate Ore - Zhou, Fang; Liu, Qi; Liu, Xu; Li, Wanchun; Feng, Jian; Chi, Ru-an (Frontiers in Materials, 2020)
The phosphate ore flotation is achieved through the surface electrical behavior difference among apatite, dolomite and quartz, but it is usually affected by the dissolved ions from pulp, especially Ca2+ and Mg2+. The zeta potentials of apatite, dolomite, quartz and phosphate ore in different solutions were measured to discuss the surface electrical behaviors of them in this study. It was found that the apatite, dolomite and phosphate ore supernatants have limited impact on the zeta potentials of the respective surfaces themselves, but the surface electrical behaviors of apatite and dolomite in the supernatant of the other is similar to the supernatant mineral source. This will increase the separation difficulty of apatite from dolomite in the phosphate ore flotation process. The negative zeta-potential of apatite, dolomite, quartz and phosphate ore increase in the presence of Ca2+ and Mg2+. Moreover, a more zeta potential increase in presence of Ca2+ than Mg2+ was investigated, suggesting a stronger influence of Ca2+ than Mg2+ on the surface electrical behaviors of ores.